2018
DOI: 10.4314/njt.v36i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Use of standalone photovoltaic system for office building: the case study of national centre for hydropower research and development, Nigeria

Abstract: This paper presents the design of a cost effective energy system for National Centre for Hydropower Research and Development (NACHRED) building to supply its daily energy requirements. The daily hourly load demand of the building was measured with FLUKE 434 Series II Energy Analyzer. The measurement was grouped into two namely: category 1 and category 2. In category 1, the essential electrical load demand excluding air conditioner system was measured for 3 consecutive days while in category 2 the total daily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…One study conducted a simulation and feasibility study of a battery HPS/solar PhotoVoltaic (PV) system and reported a 59.6% reduction in NPC and an 80.7% reduction in operating cost for LCOE compared to conventional methods [24]. The HOMER software conducted the reliability and stability of an energy-efficient system and self-sufficient buildings in terms of energy generation [25]. Another study examined the potential of a standalone hybrid system that includes a wind turbine and PV to meet the energy demands of a hotel in Jordan and found that a 10 kW wind turbine and a 20 kW PV system could adequately meet the needs with a payback time of 11 years [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study conducted a simulation and feasibility study of a battery HPS/solar PhotoVoltaic (PV) system and reported a 59.6% reduction in NPC and an 80.7% reduction in operating cost for LCOE compared to conventional methods [24]. The HOMER software conducted the reliability and stability of an energy-efficient system and self-sufficient buildings in terms of energy generation [25]. Another study examined the potential of a standalone hybrid system that includes a wind turbine and PV to meet the energy demands of a hotel in Jordan and found that a 10 kW wind turbine and a 20 kW PV system could adequately meet the needs with a payback time of 11 years [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, an SAPV system was designed using HOMER for an office building in Kwara State, Nigeria to meet two different load demands, i.e. with and without the air-conditioning loads [10]. The COE for the system without air-conditioning loads was found to be $0.539/kWh while the COE for system with air-conditioning loads was found to be $0.542/kWh.…”
Section: Introductionmentioning
confidence: 99%